The Iconography of Thanatos, the God of Death in Greek art, and the Macabre from Classical Sensitivity - González Zymla, Herbert (Eikón / Imago, 2021)
Within the collective imagination of the ancient world, Thanatos was the God of Death, son of Nix, the Night, and Erebus, the Darkness of Hades. The identification of the main literary and iconographic sources bequeathed by the Classical World about Thanatos allows both the establishment of essential figurative types and, together with them, the deciphering of some of the keys related to the conception of life and death that both the Greeks and the Romans had. Together with his brother, Hypnos, The Sleep, Thanatos was responsible for the preliminary stage to the journey of the deceased to the afterlife. Both of them moved the defunct, in body and soul, from his death-place to where the funeral rites were going to be celebrated. There the body would be consumed by the fire and the soul would commence its journey to The Hades, first driven by Hermes and then by Charon. Most of the iconographic examples of God Thanatos that have been identified correspond to Greek, Etruscan and Neoclassical art. Obviously, for the most part, they are works related to funerary environments. Literary sources and the iconography of Thanatos are analyzed in relation to his divine genealogy, as described by Hesiod in the Theogony; the myth of the transfer of Sarpedon´s corpse from the place where he died to the place where he was honored, as it appears in Himer´s Iliad; and the treatment of Thanatos in the tragic poets.